Immunologic mechanisms in asthma - Boonpiyathad, Tadech; Sözener, Zeynep Celebi; Satitsuksanoa, Pattraporn; Akdis, Cezmi A. (Seminars in immunology, 2019)
Asthma is a chronic airway disease, which affects more than 300 million people. The pathogenesis of asthma exhibits marked heterogeneity with many phenotypes defining visible characteristics and endotypes defining molecular mechanisms. With the evolution of novel biological therapies, patients, who do not-respond to conventional asthma therapy require novel biologic medications, such as anti-IgE, anti-IL-5 and anti-IL4/IL13 to control asthma symptoms. It is increasingly important for physicians to understand immunopathology of asthma and to characterize asthma phenotypes. Asthma is associated with immune system activation, airway hyperresponsiveness (AHR), epithelial cell activation, mucus overproduction and airway remodeling. Both innate and adaptive immunity play roles in immunologic mechanisms of asthma. Type 2 asthma with eosinophilia is a common phenotype in asthma. It occurs with and without visible allergy. The type 2 endotype comprises; T helper type 2 (Th2) cells, type 2 innate lymphoid cells (ILC2), IgE-secreting B cells and eosinophils. Eosinophilic nonallergic asthma is ILC2 predominated, which produces IL-5 to recruit eosinophil into the mucosal airway. The second major subgroup of asthma is non-type 2 asthma, which contains heterogeneous group of endoypes and phenotypes, such as exercise-induced asthma, obesity induced asthma, etc. Neutrophilic asthma is not induced by allergens but can be induced by infections, cigarette smoke and pollution. IL-17 which is produced by Th17 cells and type 3 ILCs, can stimulate neutrophilic airway inflammation. Macrophages, dendritic cells and NKT cells are all capable of producing cytokines that are known to contribute in allergic and nonallergic asthma. Bronchial epithelial cell activation and release of cytokines, such as IL-33, IL-25 and TSLP play a major role in asthma. Especially, allergens or environmental exposure to toxic agents, such as pollutants, diesel exhaust, detergents may affect the epithelial barrier leading to asthma development. In this review, we focus on the immunologic mechanism of heterogenous asthma phenotypes.